Decline of Humoral and Cellular Immune Responses Against SARS-CoV-2 6 Months After Full BNT162b2 Vaccination in Hospital Healthcare Workers - Bonnet, Benjamin; Chabrolles, Hélène; Archimbaud, Christine; Brebion, Amélie; Cosme, Justine; Dutheil, Frédéric; Lambert, Céline; Junda, Maud; Mirand, Audrey; Ollier, Amandine; Pereira, Bruno; Regagnon, Christel; et al. (Frontiers in Immunology, 2022)
Clinical trials and real-world evidence on COVID-19 vaccines have shown their effectiveness against severe disease and death but the durability of protection remains unknown. We analysed the humoral and T-cell immune responses in 110 healthcare workers (HCWs) vaccinated according to the manufacturer’s recommended schedule of dose 2 three weeks after dose 1 from a prospective on-going cohort in early 2021, 3 and 6 months after full vaccination with the BNT162b2 mRNA vaccine. Anti-RBD IgG titres were lower in HCWs over 60 years old 3 months after the second dose (p=0.03) and declined in all the subjects between 3 and 6 months with a median percentage change of -58.5%, irrespective of age and baseline comorbidities. Specific T-cell response measured by IGRA declined over time by at least 42% (median) in 91 HCWs and increased by 33% (median) in 17 others. Six HCWs had a negative T-cell response at 6 months. Ongoing follow-up should provide correlates of long-term protection according to the different immune response profiles observed. COVIDM study was registered under the number NCT04896788 on clinicaltrials.gov